2019
DOI: 10.1116/1.5089919
|View full text |Cite
|
Sign up to set email alerts
|

On the optimum off-cut angle for the growth on InP(111)B substrates by molecular beam epitaxy

Abstract: InGaAs and InAlAs epilayers were grown on InP(111)B substrates by molecular beam epitaxy. Rather than focusing on a specific off-cut angle, the growths were done on rounded wafer edges, which expose a broad spectrum of vicinal surfaces with varying off-cut angle and off-cut azimuth. The epilayers were grown at several different growth conditions by varying the growth temperature, growth rate, and arsenic (As) overpressure. The epitaxial layers were characterized at the center and the edge of the wafers using N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16] Similarly, several papers explore the MBE parameters for homoepitaxy of InP(111), as well as for heteroepitaxy of its technologically relevant latticematched alloys, In 0:52 Al 0:48 As and In 0:53 Ga 0:47 As. 4,[17][18][19] In contrast, few studies exist concerning the growth of InAs(111)A. [20][21][22][23] Reference 20 demonstrates rough InAs(111)A surfaces covered in a high density of hillocks, while Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Similarly, several papers explore the MBE parameters for homoepitaxy of InP(111), as well as for heteroepitaxy of its technologically relevant latticematched alloys, In 0:52 Al 0:48 As and In 0:53 Ga 0:47 As. 4,[17][18][19] In contrast, few studies exist concerning the growth of InAs(111)A. [20][21][22][23] Reference 20 demonstrates rough InAs(111)A surfaces covered in a high density of hillocks, while Refs.…”
Section: Introductionmentioning
confidence: 99%
“…For the growth of InGaAs on InP(111)B, we showed that a minimum misorientation angle of 0.4°is needed to avoid surface hillocks at the optimized growth conditions. 20 However, the optimum misorientation angle for InAlAs on InP(111)B was not optimized.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In our previous study, we showed that the smooth epitaxy could occur on optimally misoriented substrates regardless of the misorientation direction. The misorientation direction only affects the shape of the hillocks (i.e., being completely symmetric or asymmetric) . The [2̅11] direction was used since the facets of the pyramids are tilted toward <2̅11> azimuthal directions. , …”
Section: Resultsmentioning
confidence: 99%
“…Optimized MBE growth conditions for InGaAs and InAlAs on InP(111)A are discussed elsewhere. 15,26,27 To grow the Ge TSQDs, we adjusted T sub for TSQD growth under As 4 , closed the arsenic shutter and valve, waited 1 min, and then opened the Ge shutter. 17 Previous studies have shown that the InAlAs(111)A surface is thermally stable at these temperatures, even when the arsenic flux is removed for a short time.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We grew both InGaAs and InAlAs at a substrate temperature ( T sub ) of 510 °C, with a V/III beam equivalent pressure (BEP) ratio of 160. Optimized MBE growth conditions for InGaAs and InAlAs on InP(111)­A are discussed elsewhere. ,, …”
Section: Experimental Methodsmentioning
confidence: 99%